Optimisation of secondary prevention of stroke: a qualitative study of stroke patients' beliefs, concerns and difficulties with their medicines. (10th March 2014) - Souter, Caroline; Kinnear, Anne; Kinnear, Moira; Mead, Gillian
Abstract: Objectives: The objectives of this study are to explore stroke patients' and carers' beliefs and concerns about medicines and identify the barriers to medication adherence for secondary stroke prevention. Methods: Qualitative semistructured one-on-one interviews were conducted with 30 patients with diagnosis of stroke. Interviews were analysed using the framework approach. Key findings: The study suggests that stroke patients' and carers' perceptions of their medicines may influence medicine-taking behaviour. In some cases when beliefs outweighed concerns, practical barriers prevented participants taking their medicines. Negative beliefs about a medicine were strong enough to prevent some participants starting a new medicine. Participants' actions were influenced by the perceived consequences of not taking the medicine and the impact of the adverse effect on their quality of life. Concerns lessened with time with no adverse effects. The importance of the role of the carer and of a medicine-taking routine was evident. Participants reported the inadequacy of information provision and the desire to have more written and verbal information. Some reported total lack of contact with their general practitioner or community pharmacist after hospital discharge. Conclusions: Many of the difficulties stroke patients have adhering to secondary prevention strategies are potentially preventable with tailored information provision and appropriate monitoring and follow-up by primary healthcare professionals. We have designed an intervention addressing the identified barriers to medicine taking, the impact of which is currently being measured in a randomised controlled trial of a pharmacist-led home-based clinical medication review in stroke patients.